Long intergenic non-coding RNA 1939 eliminates proliferation and migration of human renal cell carcinoma (RCC) cells by down-regulation of miR-154 - Rongyuan Zhang; Weijie Zhang; Baocai Xu; Chuan Lv; Jianquan Hou; Guangbo Zhang (Artificial Cells, Nanomedicine, and Biotechnology)
Renal carcinoma (RCC) is widely accepted as a malignant tumour of urinary system. Long intergenic non-coding RNA 1939 (LINC01939) is a novel lncRNA which was found to be down-regulated in RCC. Thus, we set out to explore the effect and regulation mechanism of LINC01939 in RCC. LINC01939 and miR-154 in RCC tissues and cell lines were detected using qRT-PCR assay. To examine cellular viability of ACHN and CAKI-1 cells, cell counting kit-8 (CCK-8) assay was exploited here. Flow cytometric analysis was conducted to examine apoptosis. Cell mobility was valued through wound healing assays. Western blotting was applied for examination of proteins related to proliferation, apoptosis, migration and Wnt/β-catenin/Notch. LINC01939 was down-regulated in RCC tissues. LINC01939 overexpression impeded proliferation and migration, and induced apoptosis. Further study found that the overexpression of LINC01939 strongly suppressed miR-154 expression. Then, the inhibiting effect of overexpressed LINC01939 on proliferation and mobility and the promoting role of LINC01939 in apoptosis were abolished by the combination of miR-154 mimic. Finally, we found that overexpressed LINC01939 inactivated Wnt/β-catenin and Notch through suppressing miR-154. Up-regulation of LINC01939 inhibited proliferation and migration of RCC cells by down-regulating miR-154.